2017
DOI: 10.4155/bio-2017-0105
|View full text |Cite
|
Sign up to set email alerts
|

2D-LC–MS/MS to Measure Cleaved High-Molecular-Weight Kininogen in Human Plasma as A Biomarker for C1-Inh-Hae

Abstract: Aim: C1-INH-HAE is caused by activation of plasma kallikrein which subsequently cleaves high-molecular-weight kininogen (HMWK) to generate bradykinin and cHMWK. Materials & methods: A novel ion-pair 2D LC-MS/MS assay was developed to measure the 46 kDa cHMWK in plasma as a biomarker for C1-INH-HAE. The sample preparation included sodium dodecyl sulfate denaturation, methanol crash, chymotryptic digestion and peptide enrichment by solid phase extraction. Results: The LLOQ was 200 ng/ml. The overall cHMWK recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Semi-quantification of results can be done by scanning gels [ 13 ]. New effective methods for cHK measurement are based on a monoclonal antibody ELISA [ 52 ] and modification of liquid chromatography–mass spectrometry [ 53 ]. Cugno et al observed, in patients with C1-INH-HAE, high levels of cHK during attacks and normal levels during remission [ 54 , 55 ].…”
Section: Biochemical Biomarkersmentioning
confidence: 99%
“…Semi-quantification of results can be done by scanning gels [ 13 ]. New effective methods for cHK measurement are based on a monoclonal antibody ELISA [ 52 ] and modification of liquid chromatography–mass spectrometry [ 53 ]. Cugno et al observed, in patients with C1-INH-HAE, high levels of cHK during attacks and normal levels during remission [ 54 , 55 ].…”
Section: Biochemical Biomarkersmentioning
confidence: 99%
“…Another proposed approach to address bradykinin-mediated angioedema is the analysis of spontaneous amidase activity in plasma. The measurement of spontaneous amidase activity refers to the ability of different serine proteases, such as plasma kallikrein, factor XII, plasmin, and tissue plasminogen activator to hydrolyze specific synthetic peptides in vitro (usually HD-Pro-Phe-Arg-pNA or Z-Phe-Arg-AMC-HCl), and it is frequently used to evaluate the activation of the kallikrein-kinin system (65)(66)(67). Since most of the serine proteases circulate as zymogens in plasma, the activation of the proenzymes of the kallikreinkinin system can be achieved by the addition of negatively charged molecules such as dextran sulfate.…”
Section: Perspectives Of Tests For Bradykinin-mediated Angioedemamentioning
confidence: 99%
“…This is mainly due to its wide availability for a reasonable price and its ability to cleave proteins into peptides of a size that is compatible with LC-MS/MS analysis on a triple quadrupole. If no suitable peptides are formed by trypsin, alternative enzymes such as chymotrypsin [5] or Glu-C [6] can also be used, or even chemical digestion, such as in the case of the presence of an acid-labile amide bond in the protein of interest [7].…”
Section: Digestionmentioning
confidence: 99%